Dexamethasone interferes with osteoblasts formation during osteogenesis through altering IGF‐1‐mediated angiogenesis. Issue 9 (22nd January 2019) - Xu, Shengsong; Guo, Rui; Li, Pei‐Zhi; Li, Ke; Yan, Yu; Chen, Jianlong; Wang, Guang; Brand‐Saberi, Beate; Yang, Xuesong; Cheng, Xin
Abstract: Dexamethasone (Dex), a synthetic glucocorticoid (GC) with long‐lasting treatment effects, has been proved to exert a modulatory effect on osteoblast proliferation and differentiation during embryonic osteogenesis. However, it is still controversial if Dex exposure influences endochondral ossification and the underlying mechanism. In this study, chick embryos in vivo and preosteoblast cell cultures in vitro were utilized to investigate the effects of Dex on osteoblast formation and differentiation during the skeletal development. We first demonstrated that Dex exposure could shorten the long bones of 17‐day chick embryos in vivo, and also downregulated the expressions of osteogenesis‐related genes. Next, we established that Dex exposure inhibited the proliferation and viability of preosteoblasts‐MC3TC‐E1 cells, and the addition of insulin‐like growth factor 1 (IGF‐1) could dramatically rescue these negative effects. On the basis of remarkable changes in the rescue experiments, we next verified the important role of angiogenesis in osteogenesis by culturing isolated embryonic phalanges in Dulbecco's modified Eagle's medium culture or on the chick chorioallantoic membrane (CAM). Then, we transplanted MC3T3‐E1 cell masses onto the CAM. The data showed that Dex exposure reduced the vessel density within the developed cell mass, concomitantly with the downregulation of IGF‐1 pathway. We verified that the inhibition of blood vessel formation caused by Dex could be rescued by IGF‐1 treatment using the CAM angiogenesis model. Eventually, we demonstrated that the shortened length of the phalanges in the presence of Dex could be reversed by IGF‐1 addition. In summary, these findings suggested that the inhibition of Igf‐1 signal caused by Dex exposure exerts a detrimental impact on the formation of osteoblasts and angiogenesis, which consequently shortens long bones during osteogenesis. Abstract : Our findings suggested that the inhibition of insulin‐like growth factor 1 signal caused by dexamethasone exposure exerts a detrimental impact on the formation of osteoblasts and angiogenesis, which consequently shortens long bones during osteogenesis.